Lunar Calendar from the Mordovian Starosotensky Burial Ground - Vladimir V. Stavitsky (Финно-угорский мир)
Introduction. The lunar calendar is one of the oldest methods of counting the days of the year. In the Mordovian language, the lexeme ‘‘kov’’ denotes both the moon and a calendar month. Consequently, the medieval Mordovians had a lunar calendar, but no material evidence of this has been previously presented. The problem of this study lies in the insufficient informativeness of available ethnographic and linguistic sources, which lack chronological data. The aim of the research is to identify material evidence of the existence of a lunar calendar among the medieval Mordovians and to clarify the chronology of its usage.